The Repercussions of the Russian-Ukrainian Crisis on Arab National security during the Period (2021-2023) - Rawashdeh, Mohammad Salim; Shboul, Hani Ahmed (Dirasat: Human and Social Sciences, 2025)
Objectives: The study aimed to identify the repercussions of the Russian-Ukrainian crisis on Arab national security during the period (2021-2023), trying to address many concerns, the most important of which are: The concept, determinants and most important challenges facing Arab national security? What is the nature and repercussions of the Russian-Ukrainian war on Arab national security? Methods: The study used the variables analysis approach and survey using content analysis approach as well as the poetics of regional hegemony theory via media analysis. Results: The study results showed that despite the availability of all factors that allow Arab countries to achieve the highest levels of strength and balance of power in terms of creating a prominent structure for Arab national security, Arab countries are still suffering from severe shortages in food production, industries, technology and comprehensive security. Conclusions: The study concluded that that the Russian-Ukrainian war had and will have great repercussions and challenges on Arab national security as well as on international security simultaneously.